2018
DOI: 10.1021/acs.jpcb.7b09497
|View full text |Cite
|
Sign up to set email alerts
|

Ultraslow Phase Transitions in an Anion–Anion Hydrogen-Bonded Ionic Liquid

Abstract: A Raman spectroscopy study of 1-ethyl-3-methylimidazolium hydrogen sulfate, [CCim][HSO], as a function of temperature, has been performed to reveal the role played by anion-anion hydrogen bond on the phase transitions of this ionic liquid. Anion-anion hydrogen bonding implies high viscosity, good glass-forming ability, and also moderate fragility of [CCim][HSO] in comparison with other ionic liquids. Heating [CCim][HSO] from the glassy phase results in cold crystallization at ∼245 K. A solid-solid transition (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 43 publications
2
12
0
Order By: Relevance
“…Note that the phase transition temperatures suggested by the DSC with its high sweep rate cannot directly be compared with the phase transition temperatures observed using POM or X‐ray studies, which require small temperature sweep rates to reach the equilibrium. That DSC showed several phase transitions was, in fact, not surprising, as seen for other imidazolium ILs with an HSO 4 − ‐counter‐anion …”
Section: Resultssupporting
confidence: 59%
See 1 more Smart Citation
“…Note that the phase transition temperatures suggested by the DSC with its high sweep rate cannot directly be compared with the phase transition temperatures observed using POM or X‐ray studies, which require small temperature sweep rates to reach the equilibrium. That DSC showed several phase transitions was, in fact, not surprising, as seen for other imidazolium ILs with an HSO 4 − ‐counter‐anion …”
Section: Resultssupporting
confidence: 59%
“…This has previously led to hydrogen bonded HSO 4 − ‐chains in CsHSO 4 at low temperatures . Furthermore, in other imidazolium ILs, this counter‐ion has a strong role to control the assembly due to formation of hydrogen bonds between the counter‐ions . Not surprisingly, also in the present DiC 9 ‐IL, the calculated structure suggests formation of hydrogen bonded chains of HSO 4 − in the b ‐direction with SS distances of 0.4 nm and corresponding H‐bond distance of 0.14 nm (Figure S9, Supporting Information).…”
Section: Resultssupporting
confidence: 57%
“…[6][7][8][9] Calorimetric measurements have shown that ionic liquids may exhibit complicated patterns of phase transitions including crystallization, glass transition, solid-solid transitions, and complex pre-melting behavior. 10,11,12,13,14,15 At least three characteristic patterns of thermal behavior have been found by differential scanning calorimetry (DSC) of ionic liquids: i. crystallization; ii. supercooling and glass transition; iii.…”
Section: Introductionmentioning
confidence: 99%
“…[C2C1im][HSO4], the glass forming ability follows as a consequence of the high viscosity. 14,24 Then the interesting issue is the reason of high viscosity, in the case of [C2C1im][HSO4] being the occurrence of anion-anion hydrogen bonded structures. 14,24 When the ethyl chain is replaced by a benzyl group (1-benzyl-3methylimidazolium, [BzC1im] + ) low viscosity liquids can be obtained, e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation